What matters versus what's the matter – exploring perceptions of person-centred practice in nursing and physiotherapy social media communities: a qualitative study. (November 2018) - Ward, Andrew; Eng, Clarissa; McCue, Victoria; Stewart, Ryan; Strain, Kerri; McCormack, Brendan; Dukhu, Sharisse; Thomas, Janet; Bulley, Cathy
No abstract available